Variation of the Anticlines Vergency in the Iraqi Zagros Folds Belt and Its Tectonic Indications - Ayyed Hussein Ward; Thair Mudhir Fahmi; Hasnaa Saleh Khalaf (Tikrit Journal of Pure Science, 2020)
Folds of northern Iraq are considered integral part for the Western Zagros Fold – Thrust Belt. The growth of these folds was due to inversion displacement on inherited listric faults. This research deal with the relationship between the folds vergency and the faults that propagated folds, where that the dip of the back limb (gentle limb) for the fold is parallel to the thrust fault surface that propagated the fold, and the vergency of the fold determined by the forelimb (steep limb) situation. As a results, the folds of the high folded zone and of the western part of the low folded zone showed suture ( N and NE) vergency and foreland (S and SW) vergency, while the eastern part of the low fold zone showed foreland (S and SW) vergency only. The appearance of the suture and foreland vergency within the high folds considered as indication to the high tectonic development conformable with the location of these folds in the Iraqi Zagros Fold Belt, while the appearance of the suture and foreland vergency in the western part of the low folded zone attributed to the more tectonic development of this part in comparison with the eastern part of the zone that there folds appeared foreland vergencies only, or to the influence of the evaporite beds for Fatha formation in this part.